IDENTIFICATION THE SOURCES OF PAHS IN CLUJ-NAPOCA’S CITY ATMOSPHERE USING MOSS AS BIOMONITORS - ROTARU, Andreea-Maria; POP, Sorin; PĂNESCU, Vlad; BELDEAN-GALEA, Mihail Simion (Studia Universitatis Babeș-Bolyai Ambientum, 2017)
This study aims to determine the concentrations of PAHs in Cluj-Napoca’s city atmosphere using moss as biomonitors. Samples from different neighborhoods of Cluj-Napoca city were collected and analyzed by gas chromatography coupled with mass spectrometry. The concentrations of individual PAHs ranged from 0.61 µg kg-1 (chrysene) to 353.6 µg kg-1 (Indeno(1,2,3 -cd)pyrene), and the ΣPAHs ranged from 92.61 µg kg-1 to 353.6 µg kg-1 with a mean value of 329.23 µg kg-1. Residential areas characterized by both low population density and traffic intensity had the lowest concentration levels of ΣPAHs in moss samples, below 200 µg kg-1. Levels of concentration between 200 and 300 µg kg-1 were obtain in similar residential areas, but with more intense traffic. The locations that had PAHs concentration levels in moss exceeding 300 µg kg-1 are either industrial areas or neighborhoods with intense traffic. In all the study’s locations the main emission source, according to PAHs diagnostic ratios, is pyrogenic, mainly originating from traffic emissions. The FL/ (FL+PYR) and FLA/ (FLA+ PYR) ratios indicate that in some cases there also is a petrogenic source. In a cross examination however, it can easily be seen that the main apportion for all the location is from pyrogenic sources.